Process design for processed Kashar cheese (a pasta-filata cheese) by means of microbial transglutaminase: Effect on physical properties, yield and proteolysis. (May 2020) - Topcu, Ali; Bulat, Tugba; Özer, Barbaros
Abstract: Cheese industry has long been interested in improving the quality and functionality of cheese to meet consumers' demand as well as reducing the production costs by using different manufacturing strategies. In this study, the effects of microbial transglutaminase (mTG) on the yield, proteolysis and physical properties of processed Kashar cheese were evaluated. The mTG level used was 0.75 U/g protein and the concentrations of emulsifying salt (ES) mixture were 0.8, 1.0 and 1.2 g/100 g cheese curd (w/w). The increase in the moisture adjusted yield of cheeses were between 1.68 and 2.00% as relative change compared to control cheese. The cheeses had similar melting profile with the control cheese. The rheological and textural properties of the cheeses were different from the control cheese. The ES concentration and addition of mTG had an impact on the proteolysis but it did not affect meltability in current concentration. To conclude, the yield of processed Kashar cheese may well be increased to a satisfactory level without adversely affecting the physical characteristics of the end product. Highlights: Microbial transglutaminase (mTG) increased the yield in processed Kashar cheese. mTG slightly slowed down proteolysis in cheese. mTG-treated cheeses made from preacidified milks were successfully melted during scalding. The combination of mTG and emulsifying salts resulted in a harder cheese body.